Generation and characterization of two induced pluripotent stem cell lines (ICGi052-A and ICGi052-B) from a patient with frontotemporal dementia with parkinsonism-17 associated with the pathological variant c.2013T>G in the MAPT gene - E. V. Grigor’eva; A. A. Malakhova; E. S. Yarkova; J. M. Minina; Y. V. Vyatkin; J. A. Nadtochy; E. A. Khabarova; J. A. Rzaev; S. P. Medvedev; S. M. Zakian (Вавиловский журнал генетики и селекции)
Frontotemporal dementia with parkinsonism-17 is a neurodegenerative disease characterised by pathological aggregation of the tau protein with the formation of neurofibrillary tangles and subsequent neuronal death. The inherited form of frontotemporal dementia can be caused by mutations in several genes, including the MAPT gene on chromosome 17, which encodes the tau protein. As there are currently no medically approved treatments for frontotemporal dementia, there is an urgent need for research using in vitro cell models to understand the molecular genetic mechanisms that lead to the development of the disease, to identify targets for therapeutic intervention and to test potential drugs to prevent neuronal death. Analysis of exome sequencing data from a 46-year-old patient with a clinical diagnosis of Parkinson’s disease revealed the presence of the pathological variant c.2013T>G (rs63750756) in the MAPT gene, which is associated with frontotemporal dementia with parkinsonism-17. By reprogramming the patient’s peripheral blood mononuclear cells, we obtained induced pluripotent stem cells (iPSCs). Two iPSC lines were characterised in detail. Reprogramming was performed by transfection with non-integrating episomal vectors expressing the OCT4, SOX2, KLF4, LIN28, L-MYC and mp53DD proteins. The iPSC lines ICGi052-A and ICGi052-B proliferate stably, form colonies with a morphology characteristic of human pluripotent cells, have a normal diploid karyotype (46,XX), express endogenous alkaline phosphatase and pluripotency markers (OCT4, NANOG, SSEA-4 and TRA-1-60) and are able to differentiate into derivatives of three germ layers: ento-, ecto- and mesoderm. The iPSC lines obtained and characterised in detail in this work represent a unique tool for studying the molecular genetic mechanisms of the pathogenesis of frontotemporal dementia with parkinsonism-17, as well as for testing potential drugs in vitro.